Epigenetic Instability of Cytokine and Transcription Factor Gene Loci Underlies Plasticity of the T helper 17 Cell Lineage - Mukasa, Ryuta (2010)
Phenotypic plasticity of T helper 17 (Th17) cells suggests instability of chromatin structure of key genes of this lineage. Here we identify epigenetic modifications across the clustered Il17a and Il17f, and Ifng loci before and after differential IL-12 or TGFβ signaling, which induce divergent fates of Th17 cell precursors. We find that Th17 precursors have substantial remodeling of the Ifng locus but undergo critical additional modifications to enable high-level expression when stimulated by IL-12. Permissive modifications across the Il17a-Il17f locus are amplified by TGFβ signaling in Th17 cells, but are rapidly reversed downstream of IL-12–induced, STAT4– and T-bet–mediated silencing of the Rorc gene. These findings reveal substantial chromatin instability of key transcription factor and cytokine genes of Th17 cells and support a model of Th17 lineage plasticity in which cell-extrinsic factors modulate Th17 cell fates through differential effects on the epigenetic status of Th17 lineage factors.